Implementasi Pendekatan Pengembangan Kurikulum dalam Kurikulum Merdeka: Studi Integrasi Kurikulum Berbasis Cinta dan Deep Learning di Lembaga Pendidikan Islam - Muhammad Rafi Nahwal Firdausi; Naila Mahdiya Mussofa; Fathur Rohman (STKIP Subang, 2026)
Curriculum development is a strategic process that determines the direction and quality of national education. The dynamics of social change, technological advancement, and 21st-century competency demands urge educational institutions, particularly those under the Ministry of Religious Affairs (Kemenag), to adaptively adopt and integrate various curriculum approaches. This article aims to analyze the implementation of curriculum development approaches within the Merdeka Curriculum, specifically through the integration of Love-Based Curriculum (KBC) and Deep Learning as instructional approaches in Islamic educational institutions. The study employs a descriptive qualitative approach with data collected through in-depth interviews and documentation. Data analysis follows the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the Merdeka Curriculum remains the primary framework, while KBC is positioned as an integrative approach embedded across all learning components, including intracurricular, cocurricular, extracurricular activities, and school culture. Deep Learning functions as a reinforcement for in-depth learning orientation rather than a standalone curriculum. The five love values in KBC—love for Allah and His Prophet, love for oneself, love for the environment, love for the homeland, and love for others—are contextually integrated into every learning material. These findings reveal that curriculum implementation in Kemenag educational institutions reflects an integrative approach that harmonizes academic orientation, religious values, and holistic character formation